Studying the Personality of Babur and his Government, Creativity and Scientific-Creative Heritage (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the material and spiritual wealth of Zahiriddin Muhammad Babur and the Baburi dynasty, the scientific and creative heritage of Zahiriddin Muhammad Babur, statecraft and military activity, the researches carried out on the extensive study of the Baburi dynasty, rare manuscripts, antiques, rare manuscripts, and ancient books, which are kept in world museums. , works of art, etc., recognition by the world community, research conducted by our republic and foreign scientists and their comparative analysis are described